Synthesis of Triazole Schiff’s Base Derivatives and Their Inhibitory Kinetics on Tyrosinase Activity - Yu, Feng; Jia, Yu-Long; Wang, Hui-Fang; Zheng, Jing; Cui, Yi; Fang, Xin-Yu; Zhang, Lin-Min; Chen, Qing-Xi (PloS one, 2015)
In the present study, new Schiff's base derivatives: (Z)-4-amino-5-(2-(3- fluorobenzylidene)hydrazinyl)-4H-1,2,4-triazole-3-thiol (Y1), (Z)-3-((2-(4-amino-5- mercapto-4H-1,2,4-triazol-3-yl)hydrazono)methyl)phenol (Y2), (Z)-2-((2-(4-amino-5- mercapto-4H-1,2,4-triazol-3-yl)hydrazono)methyl)phenol (Y3) and 3-((Z)-(2-(4- (((E)-3-hydroxybenzylidene)amino)-5-mercapto-4H-1,2,4-triazol-3-yl)hydrazono)methyl)phenol (Y4) were synthesized and their structures were characterized by LC-MS, IR and 1H NMR. The inhibitory effects of these compounds on tyrosinase activites were evaluated. Compounds Y1, Y2 and Y3 showed potent inhibitory effects with respective IC50 value of 12.5, 7.0 and 1.5 μM on the diphenolase activities. Moreover, the inhibition mechanisms were determined to be reversible and mixed types. Interactions of the compounds with tyrosinase were further analyzed by fluorescence quenching, copper interaction, and molecular simulation assays. The results together with the anti-tyrosinase activities data indicated that substitution on the second position of benzene ring showed superior ant-ityrosinase activities than that on third position, and that hydroxyl substitutes were better than fluorine substitutes. In addition, two benzene rings connecting to the triazole ring would produce larger steric hindrance, and affect the bonding between tyrosinase and inhibitors to decrease the inhibitory effects. The anti-tyrosinase effects of these compounds were in contrast to their antioxidant activities. In summary, this research will contribute to the development and design of antityrosinase agents.